The multiple loop antenna for enhanced readability performances of near-field UHFRFID applications - Rassamitut Pansomboon; Chuwong Phongcharoenpanich (My University, 2016)
This research is concerned with a multiple loop antenna applicable to near field ultra-high frequency (UHF) radio frequency identification (RFID). The proposed multi-loop antenna is configured to induce the robust and even magnetic field distributions in the Hx, Hy, and Hz orientations so as to achieve the enhanced readability performances in all directions (i.e., x, y, and z). Simulations were carried out using CST Microwave Studio to determine the impedance bandwidth (|S11|<−10 dB) in the frequency range of 920–925 MHz (i.e., Thailand's UHF RFID standard) and to investigate the Hx-, Hy-, and Hz-oriented magnetic field distributions. A prototype antenna of 14 cm × 16 cm × 0.6 mm (W × L × H) in overall dimension was subsequently fabricated on an FR4 substrate connected to a coaxial cable. In this research, the Hx-, Hy-, and Hz-oriented magnetic field distributions of the prototype antenna were measured in the x-axis, y-axis, and x–y plane and are in good agreement with the simulation results. The measured readability performances in the x-, y-, and z-directions in which seven near field UHF RFID tags were deployed unobstructed (i.e., in open air) are respectively 25.27%, 31.73%, and 85.43%. Furthermore, the performances on the antenna readability with the tags attached to the microcentrifuge tubes are 30.55%, 25.90%, and 69.09% for the x-, y-, and z-directions. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:402–417, 2016.
Keywords: Loop antenna; Antenna tuner; RFID technology advancements